2007
DOI: 10.3892/or.17.1.25
|View full text |Cite
|
Sign up to set email alerts
|

Cell proliferation and tumor formation induced by eserine, an acetylcholinesterase inhibitor, in rat mammary gland

Abstract: Abstract. Environmental chemicals may be involved in the etiology of breast cancer. There is substantial evidence that breast cancer risk is associated with prolonged exposure to female hormones. Among these hormonal influences a leading role is attributed to the ovarian hormone estradiol, since breast cancer does not develop in the absence of ovaries. The rat mammary gland has special characteristics that make it an ideal organ for studying development, cell proliferation and transformation. In vivo and in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 28 publications
(36 reference statements)
0
13
0
Order By: Relevance
“…Some reports support a causal relationship between low AChE activity levels and enhanced cell proliferation and tumor formation, for instance the Calaf's group report showing that the inhibition of AChE by eserine was capable of promoting carcinogenesis in the rat mammary gland epithelium [40].…”
Section: Discussionmentioning
confidence: 97%
“…Some reports support a causal relationship between low AChE activity levels and enhanced cell proliferation and tumor formation, for instance the Calaf's group report showing that the inhibition of AChE by eserine was capable of promoting carcinogenesis in the rat mammary gland epithelium [40].…”
Section: Discussionmentioning
confidence: 97%
“…The dose of estrogen used in these experiments was lower than the previously reported one since malathion was used in combination in one of the groups and malathion alone induced mammary tumors under these conditions. In previous experiments [77] animals were treated with eserine twice a day for 10 days followed by 17β estradiol for 30 days (200 μg/100 g body weight) once a day, and in another one alone (300 μg/100 g body weight), twice a day for five days. …”
Section: Discussionmentioning
confidence: 99%
“…These data indicated that oxidant stress plays a crucial role in estrogen-induced carcinogenesis (40). Previous studies (41) have examined the effect of eserine, an acetylcholinesterase inhibitor, as are the organophosphorous compounds malathion and parathion, in the presence of 17β-estradiol on cell proliferation and tumor formation in rat mammary gland. These studies showed that eserine and 17β-estradiol induced carcinogenesis in the epithelium of rat mammary glands.…”
Section: Discussionmentioning
confidence: 99%